Foreign Exchange Intervention : A Shield Against Appreciation Winds? - Adler, Gustavo (IMF Working Papers; Working Paper ;, 2011)
This paper examines foreign exchange intervention practices and their effectiveness using a new qualitative and quantitative database for a panel of 15 economies covering 2004 - 10, with special focus on Latin America. Qualitatively, it examines institutional aspects such as declared motives, instruments employed, the use of rules versus discretion, and the degree of transparency. Quantitatively, it assesses the effectiveness of sterilized interventions in influencing the exchange rate using a two-stage IV-panel data approach to overcome endogeneity bias. Results suggest that interventions slow the pace of appreciation, but the effects decrease rapidly with the degree of capital account openness. At the same time, interventions are more effective in the context of already ?overvalued' exchange rates.